PEMBUATAN MEDIA PEMBELAJARAN E-LEARNING BERBASIS MOODLE PADA MATAKULIAH PENGANTAR APLIKASI KOMPUTER UNIVERSITAS SERAMBI MEKKAH - Syamsul Rizal; Birrul Walidain (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2019)
The article provides a general description of the Learning Application of Moodle-based e-learning and its feasibility to students of the PGSD FKIP at Serambi Mekkah University in the Introduction to Computer Applications subject. Data collection was done through examining questionnaire and interviewing students. There were various problems faced by students based for example students complaint that the access were a little slow when retrieved simultaneously. However, the content, design and technical feasibility analysis were good and it can be used in the Introduction to Application Computer subject for PGSD students at the Serambi Mekkah University.